The Implementation of Learning Management System (LMS) of English Language Education of STKIP PGRI Banjarmasin - Fathul Zannah (Universitas Syiah Kuala, 2023)
The research is about the implementation of Learning Management System (LMS) at third-semester students of English language education of STKIP PGRI Banjarmasin. E-learning divided into two types that are synchronous and asynchronous. LMS is included in the type of asynchronous learning; it means that learning activities carried out without face to face directly. STKIP PGRI Banjarmasin is one of the universities that used Moodle-based LMS as learning media. The researcher got the data for this research from observation, interview and documentations. The techniques of collecting the data were observation, interview and documentation in lecturer’s Learning Management System (LMS). The techniques of analyzing the data were data collection, data reduction, and drawing conclusion. The research was being tested validity to trustworthiness of the data.The result of the analysis shows that the Implementation of Learning Management System (LMS) at third-semester students of English language education of STKIP PGRI Banjarmasin is implemented by asynchronous system. The steps of used Learning Management System (LMS) were preparation, Contents in LMS, Teaching learning process and evaluation. The steps that lecturer did in teaching learning process using LMS were Introduction and delivering material in LMS. Learning Management System (LMS) has many features that can used by lecturer or teacher in teaching learning process. The conclusions of the research are LMS is based on digital-system and also can accessable in 24/7. Apart from LMS, lecturer can use another additional media. LMS has many various kinds of features that can be used according to the needs in learning. The evaluation system is carried out by manual sistem not on the LMS. The suggestion for campus is hopefully can hold the socialization to using LMS for lecturer, for lecturer is must to prepared well all of features in LMS for maximum used, for researcher this research can be references with the same study and also for students, it hoped that students can be active and enthusiastic in the class.